Association of the multidrug-resistance-associated protein gene (ABCC2) variants with intrahepatic cholestasis of pregnancy - Sookoian, Silvia Cristina (2008)
Objective: We hypothesized that common genetic variation at ABCC2 influences ICP susceptibility. Hence we studied the association of single nucleotide polymorphisms (SNPs) of promoter, coding and non-coding regions of ABCC2 and ICP. Patients & Methods: 70 ICP patients and 112 healthy pregnant women in the third trimester of their pregnancies were included in a cross sectional study. Four tag SNPs (rs717620 A/G; rs2756105 C/T; rs2002042 C/T; rs3740066 A/G) encompassing 70 kb in chr.10 and representing 46 polymorphic sites (r2 >0.8) were genotyped. Besides, 2 additional SNPs (rs17222723 A/T and rs8187710 G/A) were included. Results: In univariate analysis, rs2002042 and rs3740066 were significantly associated with ICP (p<0.04 and 0.01 respectively) but after multiple testing correction, only rs3740066 remained significantly associated with disease status (p<0.03). We also observed a positive association between the rs3740066 and ALT, AST, alkaline alkaline phosphatase and total and conjugated bilirubin concentrations. Consistent with the analysis of individual markers, we observed that haplotype frequency of the ABCC2 gene in ICP patients significantly differed from controls (p<0.03). Conclusion: we found an association between the rs3740066 in exon 28 of ABCC2 gene and ICP. The risk of disease for homozygous AA carriers is 4-fold higher (OR 4.44 CI 95% 1.83-10.78, p<0.001) in comparison with GG carriers.